The Global Compact on Refugees: inadequate substitute or useful complement? - Arnold-Fernández, Emily E. (Frontiers in Human Dynamics, 2023)
The Global Compact on Refugees is touted by its supporters as a soft law instrument that advances solutions for refugees in a way that complements the fundamental human rights protections afforded by the hard law Refugee Convention. In practice, however, the Global Compact appears to have replaced the Refugee Convention as the centerpiece of multilateral dialogue about states’ actions vis-à-vis refugees. This paper argues that the substitution of the Global Compact in place of the Refugee Convention is problematic from a human rights perspective because the Global Compact makes very little provision for refugees’ rights and interests, instead focusing on the rights and interests of states. The Compact thus exerts a gravitational pull that distances the forced displacement response sector from the objective of realizing refugees’ human rights. To counter this, the paper suggests a need for increased attention and deeper investment in bolstering the use of human rights treaty mechanisms and processes to enforce refugees’ human rights.